Academic Motivation as a Mediator of Social Support and Achievement Orientation: Case of Muslim High School in Indonesia - Supriyadi, Tugimin (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2024)
The study of academic motivation is essential in understanding how various factors contribute to students' educational achievements and overall well-being. This research explored the relationship between academic motivation and the mediation effects of social support on achievement orientation. Specifically, it examined how these factors interrelates and supports each other in the context of high school students. The sample for this study consisted of 225 high school students selected through convenient and cross-sectional sampling techniques. The instruments utilized included the Academic Motivation Scale (AMS) for assessing academic motivation, the Multidimensional Scale of Perceived Social Support (MSPSS) for evaluating social support, and the Achievement Goal Orientation Scale for measuring achievement orientation. To analyze the data, several statistical techniques were employed. Descriptive statistics were used to summarize the data, and Pearson correlation was applied to determine the relationships between social support and the dimensions of academic motivation. To measure the reliability of the scales, Cronbach's alpha was calculated. Additionally, regression analysis was conducted to examine the effects of social support on academic motivation and achievement goals. The findings revealed that there was no significant direct effect of social support on students' mastery and performance goal orientations. However, in terms of indirect effects, family support was found to influence academic motivation, which in turn affects achievement orientation.